Aplikasi Algoritma Euclidean dalam Produksi Jagung di Pulau Jawa - Setiawan, Ade Ripki; Kurniadi, Edi; Triska, Anita; Sylviani, Sisilia (Department of Mathematics, Faculty of Science and Technology Universitas Jambi, 2024)
Corn farming on the island of Java plays a crucial role in meeting the nation's food needs. However, variations in land conditions across provinces in Java result in differing production levels. This disparity affects the supply of corn in the market, and the selling price often does not align with farmers' expectations. Therefore, this article aims to determine the optimal timing for distributing corn, particularly on the island of Java, using the Euclidean algorithm. The Euclidean algorithm is used to calculate the greatest common divisor (gcd), which in turn is applied to determine the least common multiple (lcm). The lcm results can serve as a reference for identifying the best time to sell corn to prevent price declines. Additionally, a comparison of production levels across provinces is presented to help corn farmers understand when and where to distribute their produce to achieve maximum profit.